Teen Titans. Beast Boy - Garcia, Kami (DC Comics, 2020)
Seventeen-year-old Garfield Logan hates feeling overlooked by the cool kids in his small town of Eden, Georgia, and the clock is ticking on his senior year to make an impression and become popular. Meanwhile, his old best friends Stella and Tank just want their funny, fun-loving friend back. Then, in taking on a wild dare, Gar finds the popularity he has always wanted, but at the cost of startling changes to his body.